The Miller-Modigliani 1961 Ponzi scheme, alias "dividend irrelevance" - Paulo, Stanley; Gale, Chris (International journal of law and management, 2012)
Purpose - The purpose of this article is to expose the Miller-Modigliani 1961 Ponzi scheme that has masqueraded as a dividend irrelevance proof, and show that it constituted a Ponzi scheme at the time of publication and ever since publication. This is important especially as Miller-Modigliani 1961 stated in the first sentence of their article that their dividend irrelevance proof was targeted at corporate officials, investors and economists seeking to undertake and appraise the functioning of capital markets.Design methodology approach - The equations and notation used by Miller-Modigliani 1961 to prove dividend irrelevance were carefully considered and analysed in order to establish whether proof reliably, validly and unambiguously proved dividend irrelevance. In addition, statute on both sides of the Atlantic, UK and USA, was considered in order to ascertain the legal standing of their proof.Findings - This article shows that the Miller-Modigliani 1961 dividend irrelevance proof constituted a recipe for a Ponzi scheme in terms of statute at the time of publication and ever since publication. Since Miller-Modigliani 1961 made extensive reference to the works of eminent finance researchers and academics of the 1930s, 1940s, and 1950s, as well as to their Modigliani-Miller 1958 seminal article, and attentively present and discuss the intricacies of the arguments these researchers made to the progression of knowledge, it would be challenging to content that they were unaware or ignorant of important legislation that applied in 1961.Originality value - There is no evidence from a scrutiny of publicly available secondary sources to suggest that the Miller-Modigliani 1961 Ponzi scheme, alias "dividend irrelevance" has previously been done or published. This is surprising because the Miller-Modigliani 1961 dividend irrelevance proof has occupied a particularly prominent position in the finance literature and has been the subject of numerous studies and research projects.